Newsletter September 2021 (Medical Journals Sweden, 2021)
Editor's Choice: Patient-Reported Outcome Measures in Dermatology: A Systematic Review Rachael L. Pattinson, Nirohshah Trialonis-Suthakharan, Sunnia Gupta, Alasdair L. Henry, Jacqueline F. Lavallée, Marina Otten, Timothy Pickles, Nick Courtier, Jennifer Austin, Christine Janus, Matthias Augustin, Chris Bundy Further highlights of September: Survival of Adjuvant Drugs for Treatment of Pemphigus: A Population-based Cohort Study.  Khalaf Kridin, Christoph M. Hammers, Ralf J. Ludwig, Dana Tzur Bitan, Arnon D. Cohen Vitamin D Status in Distinct Types of Ichthyosis: Importance of Genetic Type and Severity of Scaling. Mi-Ran Kim, Vinzenz Oji, Frederic Valentin, Heiko Traupe, Jerzy-Roch Nofer, Ingrid Hausser, Hans Christian Hennies, Katja Eckl, Stefan A. Wudy, Alberto Sánchez-Guijo, Laura Kerschke, Judith Fischer, Kira Süssmuth Chronic Pruritus of Unknown Origin: Clinical Profile and Disease-Related Burden. Manuel P. Pereira, Alexandra Farcas, Claudia Zeidler, Sonja Ständer Dermoscopic Evaluation of Inflammatory Nail Disorders and Their Mimics. Sophie Soyeon Lim, Alex Chamberlain, Keunyoung Hur, Jungyoon Ohn, Byeol Han, Victoria Mar, Je-Ho Mun Prescription Behaviour and Barriers to Prescription of Biologicals for Treatment of Chronic Inflammatory Skin Diseases in Dermatological Practice in Two German Federal States. Daniela Weiss, Imke Nordhorn, Linda Tizek, Thomas Werfel, Alexander Zink, Tilo Biedermann, Stephan Traidl, Maximilian C. Schielein Societal Costs of Moderate-to-severe Atopic Dermatitis Occurring in Adulthood: A Danish Register-based Study. Jacob P. Thyssen, Andreas W. Brenneche, Maria E. Madsen, Mikkel H. Pedersen, Dennis J. Trangbaek, Christian Vestergaard